Undergraduate nursing students’ perspective on patient safety and missed care - Dimitriadou, Maria; Merkouris, Anastasios; Charalambous, Andreas; Papastavrou, Evridiki (My University, 2021)
Background: There is evidence that patient safety in nursing curriculums is not well incorporated. This does not to allow students to develop strong competences to support patient safety throughout their professional life. Aims: To explore the perspectives of undergraduate nursing students, among Greece and Cyprus populations, regarding their knowledge and attitudes on patient safetyrelated issues and missed care. Methods: A descriptive comparative study was conducted with third and fourth-year undergraduate nursing students from Cyprus (n=243) and Greece (n=481). All students were surveyed using the a) 34-item Health Professional Education Patient safety Survey (H-PEPSS) to describe students’ knowledge in the classroom and clinical setting and b) the 23-items Health Care Professionals Patient safety Assessment Curriculum survey (HPPSACS), which evaluates attitudes and c) a brief questionnaire to explore their understanding of missed care. Results: Students’ knowledge about patient safety was expressed significantly higher (p< 0.001) in classroom (mean=4.0), comparing to the clinical setting (3.7) (1-5 scale). The knowledge in the dimension “clinical aspects” was valued the highest and the dimension “Working in teams” was valued the lowest. Regarding the attitudes, the lower was reported in the topic “denial” (mean 2.1) (1-5 scale). Also, differences were recorded between countries with Cyprus reported higher level of knowledge than Greece students in most of dimensions. One third of all the students reported body hygiene as missed care incident Conclusions: The findings indicated the gap between theory and practice and the need of collaboration of the two settings. Also, the highest score in “Clinical aspects” (in both settings) reflect the fact the nursing education tend to cite on technical issues, whereas fewer tend to the more sociocultural aspects of patient safety. Relevance for nursing science in Europe: Under the absence of EU directives or curriculum guidelines on how patient safety training to be incorporated into the curriculum, study reveals important points, both theoretically and clinically, about patient safety training in two EU countries. Further research to define and update the syllabus is needed, to ensure pre-registration nursing students become engaged and therefore prepared to sustain a culture of safety.
Keywords: Nursing students; Patient safety; Undergraduate curriculum; Missed care